2014
DOI: 10.3382/ps.2014-04132
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters of egg quality traits on different pedigree layers with special focus on dynamic stiffness

Abstract: Egg quality traits are of utmost importance in layer breeding programs due to their effect on profitability in the egg production industry and on the production of quality chicks. Therefore, the aim of this study was to analyze and estimate genetic parameters of different quality traits: egg weight, breaking strength, dynamic stiffness (Kdyn), egg shape index, eggshell thickness, and albumen height. Eggs were obtained from 4 pure lines of birds. Two different tests were performed: a white breeding program, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
26
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 19 publications
6
26
1
Order By: Relevance
“…Rounder eggs were observed in the morning (P ≤ 0.001), and the measurement was also affected by the interaction between genotype and oviposition time (P ≤ 0.007), with the highest values for Bovans Brown at 12:00 h and the lowest for Bovans Sperwer at 9:00 h. This interaction may explain the contradictory results of the effect of oviposition time on egg shape index. Roland (1978) and Blanco et al (2014) observed rounder eggs in the afternoon, whereas Tumova and Ebeid (2005) observed rounder eggs in the morning. The egg shape index is associated with egg shell quality, as rounder eggs better maintain egg shell quality (Roland 1978).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Rounder eggs were observed in the morning (P ≤ 0.001), and the measurement was also affected by the interaction between genotype and oviposition time (P ≤ 0.007), with the highest values for Bovans Brown at 12:00 h and the lowest for Bovans Sperwer at 9:00 h. This interaction may explain the contradictory results of the effect of oviposition time on egg shape index. Roland (1978) and Blanco et al (2014) observed rounder eggs in the afternoon, whereas Tumova and Ebeid (2005) observed rounder eggs in the morning. The egg shape index is associated with egg shell quality, as rounder eggs better maintain egg shell quality (Roland 1978).…”
Section: Resultsmentioning
confidence: 98%
“…Commercially available genotypes produce eggs of different weights, and the proportion of egg components varies as well (Johnston and Gous 2007;Tumova and Ledvinka 2009). Notwithstanding, differences among genotypes in albumen quality (Suk and Park 2001;Tumova et al 2011), yolk quality (Tumova et al 2011), and egg shell quality (Suk and Park 2001;Tumova et al 2011;Kaur et al 2013;Blanco et al 2014) have been observed.…”
mentioning
confidence: 99%
“…Egg quality traits including egg weight (EW) , shell thickness (ST), and shell index (SI) are very important traits in layer breeding programs due to their effect on profitability in the egg production industry (Blanco et al, 2014). EW has great economic importance in poultry breeding and is considered among the major breeding objectives (Savegnago et al, 2011).…”
Section: Ovarian Morphology and Egg Quality Traits Of Egyptian Selectmentioning
confidence: 99%
“…This is due to their effect on profitability in the egg production industry and on the production of quality chicks. The ST and SI are positively correlated with breaking strength (Blanco et al, 2014). Also, eggshell with lower quality than desired may lead to contamination of the important content (yolk and albumen), compromising the dietary health of consumers and determined the number of salable eggs output in the layer industry (Cordeiro et al, 2017).…”
Section: Ovarian Morphology and Egg Quality Traits Of Egyptian Selectmentioning
confidence: 99%
See 1 more Smart Citation